Gradina Samograd / Zamina (In situ, 2024)
The paper describes previous investigations at the Samograd / Zamina hillfort near Lake Vrana, where systematic archaeological investigations have been carried out in recent years in cooperation of several institutions.
Keywords: Samograd; Zamina; Vran-Samograd; hillfort; prehistory; antiquity